Modéliser par écrit le travail pour la formation : un enjeu de mise en visibilité de compétences interactionnelles postulées comme implicites - Céline Alcade-Lebrun (Éducation et Socialisation)
This contribution aims at presenting how the modelling of table waiting activity in a gastronomic restaurant-school through a written document used for training purposes within a vocational bachelor's degree in International Catering and Hospitality Management, can participate in making interactional skills invisible, while they are crucial for proper accomplishment of work activity and novice professionalization. This analysis converges with those of other written sources and discourses for highlighting a general trend towards reducing these professions to technical gestures in the fields of professional practice and training, and in society as a whole, whereas the observation of work practices reveals a mobilization of complex interactional skills. On the basis of these findings, we set out the possibilities they offered in terms of training engineering, in order to make these complex skills visible by integrating their teaching in the curriculum and therefore enhance the training.